Dizziness and imbalance and their association with general and mental health in a community-based cross-sectional study of middle-aged individuals: the Busselton healthy ageing study - Adriana L. Smit; Robert H Eikelboom; Romola S. Bucks; Marcus D Atlas; Michael Hunter; Inge Stegeman (BMC Public Health)
Abstract Background Dizziness and imbalance are common symptoms among patients visiting healthcare providers. Current knowledge about their prevalence, impact on daily life, and associated factors is primarily based on selected samples from individuals seeking medical help, particularly older individuals. This study aimed to estimate the prevalence, symptoms, and impact of dizziness or imbalance symptoms, and to assess the association between these symptoms and their characteristics with demographic, general health, and mental health factors in middle-aged men and women from a representative, general population sample. Methods Cross-sectional data were collected from participants aged 45 to 70 years in the Busselton Healthy Ageing Study (BHAS), recruited in the City of Busselton, Western Australia. The data included physical tests and health-related questionnaires covering demographics, medical history, general and mental health, including any dizziness and imbalance symptoms and their impact on daily life. Estimates were made of the prevalence, patterns, and impact of dizziness and imbalance symptoms. Logistic regression was employed to calculate the association between demographic, mental and general health (independent variables) and the presence of dizziness or imbalance symptoms (dependent variable). Adjustments were made for sex and age as confounding factors. Results Of the 5086 participants, 1216 (23.9%) reported imbalance or dizziness, with light-headedness the most common type (64.3%; 782 of 1216). For nearly half (565; 46.5%) the imbalance or dizziness occasionally effected daily life, while for some, the impact was frequent (n = 50, 4.1%) or constant (n = 15, 1.2%). Being female (adjusted OR 2.05, 95%CI 1.79–2.34) and older in age (in years; adjusted OR 1.02, 95%CI 1.00-1.03), having a history of general health issues, and experiencing mental health problems or mental health symptoms were significantly associated with dizziness or imbalance symptoms. Conclusions Dizziness or imbalance are common symptoms among individuals aged 45 to 70 years and are associated with older age, being female, and poorer general and mental health. Given that approximately half of those affected reported occasional effects on daily life, with a few reporting frequent or constant effects, the outcomes of the study could help to raise awareness among healthcare providers about the prevalence, symptoms, and associated conditions.